2020
DOI: 10.1093/aob/mcaa140
|View full text |Cite
|
Sign up to set email alerts
|

A new genetic locus for self-compatibility in the outcrossing grass species perennial ryegrass (Lolium perenne)

Abstract: Background Self-incompatibility (SI) is a physiological mechanism that many flowering plants employ to prevent self-fertilization and maintain heterozygosity. In the grass family this is known to be controlled by a two locus (S-Z) system; however, the SI system is intrinsically leaky. Modifier genes of both the S and Z loci and a further locus, T, are known to override SI leading to self-fertilization and self-seed production. This has implications for the ecological and evolutionary success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…In our population, male gametes in the F 1 plants carrying the non-SC allele are not transmitted to the F 2 generation, causing a distorted segregation of markers linked to the SC causal gene. This has also been demonstrated recently by Slatter et al (2020), where the QTL underlying the SC locus on LG 6 in perennial ryegrass overlapped with maximum marker segregation distortion. This has relevant implications for future studies aimed at discovering novel SC sources, as the identification of distorted regions can be used as a strategy to map their position in the genome.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In our population, male gametes in the F 1 plants carrying the non-SC allele are not transmitted to the F 2 generation, causing a distorted segregation of markers linked to the SC causal gene. This has also been demonstrated recently by Slatter et al (2020), where the QTL underlying the SC locus on LG 6 in perennial ryegrass overlapped with maximum marker segregation distortion. This has relevant implications for future studies aimed at discovering novel SC sources, as the identification of distorted regions can be used as a strategy to map their position in the genome.…”
Section: Discussionsupporting
confidence: 72%
“…In our population, male gametes in the F 1 plants carrying the non-SC allele are not transmitted to the F 2 generation, causing a distorted segregation of markers linked to the SC causal gene. This has also been demonstrated recently by Slatter et al (2020), where the QTL underlying the SC locus on…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Genes underlying these loci likely have a function in the downstream cascade following the initial pollen–stigma recognition mediated by S and Z ( Do Canto et al , 2016 ). The most recent studies on non- S or non- Z sources of SC identified two genetically independent loci on LG 5 ( Arias-Aguirre et al , 2013 ; Do Canto et al , 2018 ; Cropano et al , 2021 ) and LG 6 ( Slatter et al , 2020 ) in two unrelated perennial ryegrass F 2 populations segregating for SC. In both populations, using in vitro self-pollinations ( Fig.…”
Section: Self-compatibility In the Grassesmentioning
confidence: 99%
“…Thus, differences in reproduction success rate may be dependent on the direction of reciprocal crosses and the degree of compatibility between individuals. Additional loci may be involved in the gametophytic self‐incompatibility system in Lolium spp., 12 thus the complexity of the gametophytic self‐incompatibility mating system in Lolium spp. remains unclear.…”
Section: Self‐incompatibility and Genetic Variationmentioning
confidence: 99%